Evolution of Ink Drawing in History of Art - Koževņikova, Jeļena (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2015)
Drawings created by ink, have a long history of constant developing and evolving, in the result establishing itself as a self-contained drawing technique. Many giants of art, such as Leonardo da Vinci (1452 – 1519), Titian ( 1488 – 1576), Albrecht Dürer (1471 – 1528), Marc Chagall (1887 - 1985), Pablo Picasso (1881- 1973) and Salvador Dalí (1904-1989) are well known for theirs artworks made with ink. The aim of the research: Trace and analyze evolution of ink drawing technique, through in ink created artworks of some well-known painters of 15-20 centuries.